Pope Benedict XVI’s critique of legal positivism with special regards to the role of tradition in contemporary legal systems - Žepič, Vid (Bogoslovni vestnik, 2023)
Pope Benedict XVI’s 2011 address to the Bundestag can be interpreted as a comprehensive synthesis of his perspective on the foundations of law as a subsystem within society. He underscored the paramount importance of constitutional democracy and the state, governed by an implementation of the rule of law that is both free and dedicated to upholding human dignity. Furthermore, he exhorted politicians and citizens alike to persistently pursue justice, to critically assess the law as responsible individuals, and to aspire to higher moral standards. In addition to this, he cast doubt on the adequacy of scientific legal positivism and scientism in comprehending law and the realm of reason. Stemming from his scepticism concerning the sufficiency of positivism in the formulation and interpretation of law, he emphasized the significance of European “legal heritage”. According to Benedict, this tradition originated from the cultural triangle of Jerusalem, Athens, and Rome, and serves as an indicator of a “rational legal order”. As Pope Benedict XVI’s address was directed towards scholars in the field of jurisprudence and legal historians, my analysis of the speech is accompanied by a brief examination of the role of the notion of “legal tradition” within the selected European contemporary legal systems.
Keywords: Benedikt; Bundestag speech; constitutional democracy; criticism of legal positivism; človekove pravice; European cultural triangle; evropski kulturni trikotnik; govor v Bundestagu; human rights; kritika pravnega pozitivizma; legal tradition; naravno pravo; natural law; pravno izročilo; ustavna demokracija